Eksplorasi Karakteristik Siswa, Budaya Sekolah, Proses Pembelajaran, dan Kompetensi Guru: Studi Kasus di SMA Negeri 1 Sunggal dan MAS YASPI Labuhan Deli - Amanda, Jesica; Rahmadina, Laila; Galang, Izza; Geovani, Jen; Wantri, Joko; ., Nurkadri (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Introduction to the School Field (PLP) I is the initial stage in the process of introducing the school field in the Education Bachelor's Program. The aim is to observe student characteristics, school culture, learning processes, and teacher competencies. Data collection for this research involves direct observation and the use of questionnaires. The research results show that there are efforts to develop student character, implement a good school culture, carry out effective learning processes, and have teachers with appropriate competencies.